Study of Acute Bee Paralysis Virus in Some Regions of the Republic of Armenia - Simonyan, J. T. (ՀԱԱՀ հիմնադրամ)
Bees are of great importance in agriculture. Recently, beekeeping has been threatened by various viral diseases, which forces beekeepers to look for new solutions in the fight against bee diseases. Epizootological and laboratory research was carried out in two regions (marzes) of the Republic of Armenia: Aragatsotn (Ashtarak community) and Tavush (Dilijan community). The clinical signs of the studied bees coincided with the symptoms of acute bee paralysis virus (ABPV). As a result of laboratory research, acute bee paralysis virus was confirmed in Tavush marz.
Keywords: Veterinary Science and Animal Breeding